PEMBACAAN AL-QUR’AN SURAT-SURAT PILIHAN DI PONDOK PESANTREN PUTRI DAAR AL-FURQON JANGGALAN KUDUS (STUDI LIVING QUR’AN) - Fauziah, Siti (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2014)
The author focuses on a discussion to the practices of reading certain selected surah of Qur'an in boarding schools pondok pesantren putri Daar al-Furqon Janggalan al-Furqon and its meaning in these boarding schools. The author uses social theory offered by Emile Durkheim and Karl Mannheim, religious feelings and the theory of meaning.